2019
DOI: 10.1190/int-2017-0236.1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated geologic, geophysical, and petrophysical data to construct full field geologic model of Cambrian-Ordovician and Upper Cretaceous reservoir formations, Central Western Sirte Basin, Libya

Abstract: The Cambrian-Ordovician and Upper Cretaceous formations, which are the main oil-producing formations in the central Sirte Basin, are structurally complex. The lateral and vertical heterogeneity of the reservoir formations is not well-understood, which negatively affects the performance of the reservoirs. We constructed efficient full-field static models that incorporate the lateral and vertical variation of those reservoir formations by integrating geologic and geophysical data. We determined lithology and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…1). Integrating geological and geophysical data to determine nine facies of reservoir units southeast of the Ajdabiya Trough, Abdelnabi et al [7] observed that faults mostly control the distribution and thickness of one of the reservoir units. A 3D (three-dimensional) seismic survey [8] showed a channel-like feature (of submarine origin) within the southern part of the trough (called the Intisar E field).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Integrating geological and geophysical data to determine nine facies of reservoir units southeast of the Ajdabiya Trough, Abdelnabi et al [7] observed that faults mostly control the distribution and thickness of one of the reservoir units. A 3D (three-dimensional) seismic survey [8] showed a channel-like feature (of submarine origin) within the southern part of the trough (called the Intisar E field).…”
Section: Introductionmentioning
confidence: 99%
“…That the accumulation of hydrocarbon can be controlled structurally (e.g. Abdelnabi et al [7]) is an important justification to examine the structural trends by analysing the available geophysical datasets. Hence, this study attempts to (1) obtain the structural trend and fault systems within the Ajdabiya Trough; (2) determine the depth to the magnetic basement beneath the trough.…”
Section: Introductionmentioning
confidence: 99%